Nightcap and suicidal ideation: a cross-sectional survey of lifestyle habits - Masaaki Muronaga; Takeshi Terao; Hirofumi Hirakawa; Nobuko Kawano; Akari Sakai; Mari Akase; Kentaro Kohno (Academia Mental Health & Well-Being)
Among the practical interventions for suicide prevention, we examined the lifestyle interventions. Specifically, we attempted to identify a positive lifestyle that may be associated with less suicidal ideation and a negative lifestyle that may be associated with more suicidal ideation. We investigated the association between lifestyle habits and suicidal ideation among 130 apparently healthy participants. The mean age of the participants was 49.3 years, and the majority were female (83%). A binominal logistic regression analysis using the forced entry method was conducted for the presence of suicidal ideation as a dependent variable and age, sex, sociodemographic factors, and other potentially associated variables as independent variables. In total, 14 had suicidal ideation while 116 did not. Regarding lifestyle habits, having a nightcap was significantly and directly associated with suicidal ideation (odds ratio = 11.0, p = 0.04), and the number of times per week bluefish was consumed was almost significantly and inversely associated with suicidal ideation (odds ratio = 0.44, p = 0.08). These remained unchanged even after adjusting for depression rating scores. These findings suggest a significant direct association of having a nightcap with suicidal ideation and a nearly significant inverse association of bluefish consumption with suicidal ideation. Based on our findings, consuming fewer nightcaps and more bluefish may be associated with a lower risk of suicidal ideation. Although the methodological limitations preclude any definite conclusion, the present findings provide important evidence for further prospective studies on lifestyle interventions for suicide prevention.